Modeling Approach for Determining Equivalent Optical Constants of Plastic Shading Nets under Solar Radiation Conditions - A. M. Abdel-Ghany; I. M. Al-Helal (Advances in Materials Science and Engineering)
The radiative properties of several plastic shading nets were measured under natural solar radiation conditions. We found that the plastic nets behave as homogeneous translucent materials (e.g., plastic film, plastic sheets, and glass). Based on this behavior, we suggest that it is possible to treat plastic nets as translucent materials and to characterize them with equivalent optical constants (i.e., equivalent refractive indexes, neq, and equivalent extinction coefficients, σeq). Here a physical model to determine neq and σeq of plastic nets was described in analogy to homogeneous translucent materials. We examined three groups of nets based on their color (black, black-green, and beige). Each group consisted of nets with four or five different porosities. Nets of each group had almost the same texture structure. For each group, we derived an equation for neq as a function of the net porosity and determined an average value for σeq. Once values of neq and σeq were determined, the solar radiative properties of a net could then be calculated from neq and σeq for any incident angle of solar beam radiation without the need of measurements. The present model was validated by comparing the calculated with the measured radiative properties of three nets at different incident angle of solar beam radiation. The calculated radiative properties reasonably agreed with measured values.